2019
DOI: 10.1109/access.2019.2927105
|View full text |Cite
|
Sign up to set email alerts
|

Government Subsidy Strategy for Innovative Drug R&D Based on the Inter-Firm Spillovers

Abstract: Government subsidies can supplement R&D investment within pharmaceutical firms and strengthen industry knowledge spillovers effectively. Based on the inter-firm spillovers, a differential game model is established to investigate the government subsidy strategies under the different innovative drug R&D strategies of pharmaceutical firms. With the Hamilton-Jacobi-Bellman equitation, the optimal R&D investment, the pharmaceutical technical levels, and the optimal benefits are obtained under the strategies of no p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In contrast, Fong et al showed that targeted promotions can effectively reduce consumer search activities and leads to a negative spillover effect on cross-firm purchase activity [15]. It is also common for the spillover effect to occur alongside technological progress such as drug research & development [16], big data knowledge [17], technology-based financial support systems [18], the finance and real estate industry [19], and especially in the IT market [10]. We investigate the spillover effect in the software competition economy; furthermore, we investigate how the spillover effect affects the compatibility and multihoming strategies the software firms adopt.…”
Section: Literature Reviewmentioning
confidence: 98%
“…In contrast, Fong et al showed that targeted promotions can effectively reduce consumer search activities and leads to a negative spillover effect on cross-firm purchase activity [15]. It is also common for the spillover effect to occur alongside technological progress such as drug research & development [16], big data knowledge [17], technology-based financial support systems [18], the finance and real estate industry [19], and especially in the IT market [10]. We investigate the spillover effect in the software competition economy; furthermore, we investigate how the spillover effect affects the compatibility and multihoming strategies the software firms adopt.…”
Section: Literature Reviewmentioning
confidence: 98%
“…At present, few researches have been done on the government subsidy strategies of new drug R&D considering spillover effects. However, there are some researches focus on spillover effects of R&D activities and government subsidy strategies [ 10 – 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Appropriate spillover effects help promote enterprises' R&D activities. To explore the relationship between spillover effects and R&D decisions by constructing decision-making models is one of the areas where scholars focus on research [10][11][12][13][14][15][16][17]. For example, Liu, et al [10] established a differential game model to investigate the impact of spillover effects under the different innovative drug R&D strategies of pharmaceutical firms; Xu, et al [11] established a two-stage game model to discuss the impact of technology spillovers on enterprise R&D investment; Li [12] focused on the issue of supply chain carbon emission reduction, analyzed the vertical spillover effects of green technology R&D activities on the impact of emission reduction decision variables and profits of enterprises; Huang, et al [13] established a two-stage game model and discussed the optimal spillover level and the optimal innovation R&D strategy of pharmaceutical enterprises under the conditions of both internal and inter-company spillovers; Lin [14] studied a game theoretical model that captures the interactions among three parties, and then demonstrated that knowledge spillovers have a significant impact on the eco-innovation levels, the economic benefits, and the total social welfare of supply chain; Wang [15] comprehensively considered the double marginal effect of innovation and horizontal technology spillover effect between supply chain partners, and analyzed the influence of two modes of non-cooperative R&D and cooperative R&D on innovation activities of enterprises; Sun, et al [16] focused on cooperative R&D, analyzed the impact of different R&D models on R&D investment between upstream and downstream enterprises under the conditions of horizontal and vertical spillovers; Yu [17] established a three-stage game model and analyzed the impact of environmental policy on green technological innovation of enterprises in the presence of technology spillover effect.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…During past few decades, concerns related to environmental sustainability issues has been transformed from a trendy issue to a realistic priority for consumers, industry and government organization. Thus, green subsidy scheme becomes an emerging topic of interest for practitioners and academic researchers [41]- [44]. Mass media reports also supported that subsidy provided by national or local governments affects the growth of almost every industry.…”
Section: A Literature Reviewmentioning
confidence: 99%